Whole exome sequencing is necessary to clarify ID/DD cases with de novo copy number variants of uncertain significance: Two proof‐of‐concept examples. Issue 7 (25th April 2016) - Giorgio, Elisa; Ciolfi, Andrea; Biamino, Elisa; Caputo, Viviana; Di Gregorio, Eleonora; Belligni, Elga Fabia; Calcia, Alessandro; Gaidolfi, Elena; Bruselles, Alessandro; Mancini, Cecilia; Cavalieri, Simona; Molinatto, Cristina; et al.
Abstract : Whole exome sequencing (WES) is a powerful tool to identify clinically undefined forms of intellectual disability/developmental delay (ID/DD), especially in consanguineous families. Here we report the genetic definition of two sporadic cases, with syndromic ID/DD for whom array—Comparative Genomic Hybridization (aCGH) identified a de novo copy number variant (CNV) of uncertain significance. The phenotypes included microcephaly with brachycephaly and a distinctive facies in one proband, and hypotonia in the legs and mild ataxia in the other. WES allowed identification of a functionally relevant homozygous variant affecting a known disease gene for rare syndromic ID/DD in each proband, that is, c.1423C>T (p.Arg377*) in the Trafficking Protein Particle Complex 9 ( TRAPPC9 ), and c.154T>C (p.Cys52Arg) in the Very Low Density Lipoprotein Receptor ( VLDLR ). Four mutations affecting TRAPPC9 have been previously reported, and the present finding further depicts this syndromic form of ID, which includes microcephaly with brachycephaly, corpus callosum hypoplasia, facial dysmorphism, and overweight. VLDLR‐associated cerebellar hypoplasia (VLDLR‐CH) is characterized by non‐progressive congenital ataxia and moderate‐to‐profound intellectual disability. The c.154T>C (p.Cys52Arg) mutation was associated with a very mild form of ataxia, mild intellectual disability, and cerebellar hypoplasia without cortical gyri simplification. In conclusion, we report two novel cases with rare causes of autosomal recessive ID, which document how interpreting de novo array‐CGH variants represents a challenge in consanguineous families; as such, clinical WES should be considered in diagnostic testing. © 2016 Wiley Periodicals, Inc.